Analisis Faktor Pemilihan Rute Penerbangan Oleh Taruna Sekolah Tinggi Teknologi Kedirgantaraan (STTKD) Dari Bima Menuju Yogyakarta - Syaftin Anggriani; Amelia Puspa Tamara (UNIVERSITAS MARITIM AMNI SEMARANG, 2025)
Flights from Bima to Yogyakarta can be done via transit or non-transit flight routes. The selection of flight routes carried out by cadets of the Yogyakarta Aerospace Technology College (STTKD) is quite important to know the factors that are considered in choosing the flight route to be taken, in addition, this route selection offers different alternatives in terms of travel time, ticket costs and comfort in transit and non-transit flights. With accurate information, cadets can choose the most efficient and economical option, so as to minimize their experience in traveling using air transportation. The research method used in this study is a qualitative research method. Where this research method is a method of research that is descriptive and tends to use analysis. Based on the results of data analysis of five selected sources, it shows that the selection of flight routes from Bima to Yogyakarta is influenced by several main factors such as travel time, price, and comfort. In this study, the data validity checking technique used is the triangulation technique, where the triangulation technique is to test the credibility of the data carried out. In the selection of transit flight routes, the comfort of the service is more dominant, while for non-transit flight routes, the ticket price and travel time are more dominant. Of the two flight routes, each has its own main factors in selecting a flight route, namely price, travel time, and comfort.